Native Bees in Mediterranean Semi-Arid Agroecosystems: Unravelling the Effects of Biophysical Habitat, Floral Resource, and Honeybees - Vergara-Egert, P; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier B.V., 2021)
The sustainable provision of pollination services in large regions of the Nearctic and Neotropics usually involves the coexistence of a rich assemblage of native bees and introduced bees in the same agroecosystem. This requires identifying biotic and abiotic conditions that improve the quality of semi-natural habitats surrounding agricultural crops aiming to enhance native bee survival. Here we unravel the contribution of habitat conditions, diversity of flowering plants, and honeybee abundance to the taxonomic diversity, flower visitation rates and functional trait distribution of native bees. We have selected three 1.2 km diameter experimental landscapes in a Mediterranean semi-arid agroecosystem of Central Chile, where wild bees, honeybees, and flowering plants were sampled in 83 10 × 10 m plots. The effects of eleven remote-sensing indices characterizing the habitat conditions, and their interactions with honeybee abundance have been analysed. Native bees were taxonomically richer in semi-natural habitats, with higher surface temperatures and near citrus crops. The flower visitation rates of native bees were positively affected by canopy closure and decreased in sites with a higher terrain slope. Highlands had lower honeybee abundance and native bees were more specialized. We found higher flower visitation rates of native bees on large patches with low abundance of honeybees and small patches with high abundance of honeybees. Visitation rate was also higher in sites with high flowering plant richness and with high abundance of honeybees. These findings suggest that native bees and honeybees differ in their habitat use and flowering resources. This partitioning may enhance, coexistence between these pollinator groups. We suggest that management of Mediterranean agroecosystems be focused on increasing forest canopy closure on the remnants of semi-natural habitats, while maintaining the flower diversity near crops and highlands. © 2020 The Author(s)